The influence of a new sole geometry while running - Knoepfli-Lenzin, C.; Waech, J. C.; Gülay, T.; Schellenberg, F.; Lorenzetti, S. (Journal of Sports Sciences, 2015)
Running shoe construction influences the forces experienced by the human body while running. The aim of this study was to ascertain whether the new sole architecture of the On running shoe reduces ground reaction forces compared with running barefoot or with a conventional running shoe and whether it changes the physiological parameters of running in shoes. Thirty-seven trained male participants were studied while running at submaximal speeds wearing their conventional running shoe, wearing the On running shoe and while barefoot. Additional biomechanical and physiological values were investigated to determine whether the On running shoe induced any changes in these parameters compared with conventional running shoes. The On exhibited similar ground reaction forces as conventional shoes, and these were different from the forces experienced while running barefoot, showing that the On was more similar to typical shoed running. No difference was observed in running economy between the On and a conventional shoe model. However, a slightly lower heart rate (HR) (˜1.3%) and blood lactate concentration (˜5.5%) were observed during submaximal running with the On running shoe compared with a conventional running shoe, as well as a greater lateral deviation of the centre of pressure mid-stance. The ramifications of the reduced HR and blood lactate concentration for competitive performance are unknown.